2013
DOI: 10.1093/nar/gkt043
|View full text |Cite
|
Sign up to set email alerts
|

In the absence of ATPase activity, pre-RC formation is blocked prior to MCM2-7 hexamer dimerization

Abstract: The origin recognition complex (ORC) of Saccharomyces cerevisiae binds origin DNA and cooperates with Cdc6 and Cdt1 to load the replicative helicase MCM2–7 onto DNA. Helicase loading involves two MCM2–7 hexamers that assemble into a double hexamer around double-stranded DNA. This reaction requires ORC and Cdc6 ATPase activity, but it is unknown how these proteins control MCM2–7 double hexamer formation. We demonstrate that mutations in Cdc6 sensor-2 and Walker A motifs, which are predicted to affect ATP bindin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
47
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(51 citation statements)
references
References 47 publications
(114 reference statements)
4
47
0
Order By: Relevance
“…These data provide the evidence that Cdc6, like Mcm4 and Mcm7, is essential for JH-dependent polyploidization, vitellogenesis, and egg production. It has been well established that Cdc6 is a key factor for replication origin licensing late in G 1 phase by regulating the formation of prereplication complexes that initiate DNA synthesis at S phase (37,43,58,59). Polyploidy is known to promote transcriptomic and metabolomic outputs (27,60).…”
Section: Discussionmentioning
confidence: 99%
“…These data provide the evidence that Cdc6, like Mcm4 and Mcm7, is essential for JH-dependent polyploidization, vitellogenesis, and egg production. It has been well established that Cdc6 is a key factor for replication origin licensing late in G 1 phase by regulating the formation of prereplication complexes that initiate DNA synthesis at S phase (37,43,58,59). Polyploidy is known to promote transcriptomic and metabolomic outputs (27,60).…”
Section: Discussionmentioning
confidence: 99%
“…DDK was expressed and purified as described (Evrin et al 2014). Most MBP-Mcm2-7 constructs were described in Evrin et al (2013) andFernandez-Cid et al (2013) with the exception of Mcm2-MBP. During its construction using site-directed mutagenesis, a restriction site was inserted after amino acid 712 in Mcm2.…”
Section: Methodsmentioning
confidence: 99%
“…1A, step 2; Speck et al 2005;Randell et al 2006;Speck and Stillman 2007;Tsakraklides and Bell 2010;Evrin et al 2013;Frigola et al 2013;Sun et al 2013). Using an in vitro Mcm2-7 loading system that employs a purified ORC, Cdc6, Cdt1, and Mcm2-7 hexamer and an origin-containing plasmid, we recently observed formation of a loading intermediate termed OCCM in the presence of a slowly hydrolysable ATP analog, ATP-gS, which captured a complex containing ORC-Cdc6 bound to a single Mcm2-7 hexamer and one to two copies of Cdt1 (Takara and Bell 2011;Evrin et al 2013;Sun et al 2013). A cryoelectron microscopy (cryo-EM) structure of this pre-RC intermediate showed that the AAA + ATPase domains of ORC/Cdc6 latch onto the C-terminal AAA + ATPase domains of Mcm2-7, leaving the Mcm2-7 N-terminal domains (NTDs) accessible, detailing the overall architecture of this important complex.…”
mentioning
confidence: 99%
“…ORC/Cdc6 is competent to recruit a Cdt1/ MCM2-7 heptamer ( Fig. 7D; Takara and Bell 2011;Evrin et al 2013;Sun et al 2013). Our data demonstrate that a linkage between Mcm2 and Mcm5 does not prevent OCCM formation but blocks the ATP hydrolysis-dependent establishment of a stable OCM complex, which leads to disassembly of the complex and in turn makes ORC/Cdc6 available again to re-engage Cdt1/MCM2-7 (Fig.…”
Section: Mcm2-mcm5 Linkage Affects Establishment Of Pre-rc Complexes mentioning
confidence: 99%